Investigation of the vortex ring transition using scanning Tomo-PIV - Sun, Zhengzhong; Brücker, Christoph (Experiments in fluids, 2017)
The transition of a vortex ring at Re Γ = 5030 is studied by time-resolved scanning tomographic PIV technique. The transition process is first analyzed through flow quantities such as circulation and vorticity components. Using the volumetric measurement technique, vortical organization of the vortex ring at early and late transition stages is visualized, respectively. Focus is paid to the instability phenomenon associated with transition. The present 4D flow data allows analysis of the temporal evolution of the wavenumber spectra. The dominant wavenumbers in transition are identified and the growth of their amplitude is revealed. The vortex ring transition is finally studied through the particle trajectories. A phase difference between the axial velocity and radial velocity is found at the beginning of transition; however, it is subject to change following the progression of transition. Statistical analysis on the velocity components helps to identify the aft portion of the inner ring as the one that is first to lose the original phase relation in velocity, which is caused by the secondary vortical activity during transition.